Ekstrak Air J amur Ling Zhi (Ganoderma lucidum (Leysser) Karsten) Meningkatkan Persentase Sel Limfosit T CD8+ Relatif pada Tikus yang Dipejani Doxorubicin - MUTHI IKAWATI; ANNISA KARAMITA; EDIATI EDIATI; RATNA ASMAH SUSIDARTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Cancer therapy using chemotherapeutic agents associated with many adversed side effects, including immunosupressant. The use of immunostimulator together with chemotherapeutic agent (co-chemotherapy) can be the alternative method to solve that problem. Ganoderma lucidum (Ling Zhi) has been reported to have immunostimulatory activity. The aim of this research was to evaluate the immunostimulatory activity of water extract of G. Zucidum by determining the relative CD8+ T lymphocyte cell percentage in rats induced by doxorubicin. Extraction of plant material was carried out by infusion method. Sprague Dawley female rats were divided into six groups, they were doxorubicin as control, commercial product as comparing control, 100 mg/kgBW and 450 mg/kgBW extract treatment, extract control, and without treatment control. Relative CD8+ T lymphocyte cell percentages of blood samples were obtained by flow cytometry by using Multiset program. The data were analyzed statistically using paired sample t test and one way ANOVA continued by Post Hoc test. The result showed that the water extract of G. lucidum increased the relative CD8+ T lymphocyte cell percentage in rats induced by doxorubicin. The water extract of G. lucidum is promising to be developed as co-chemotherapy immunostimulatory agent.